SPIN AND MAGNETIC EXITATION IN CHIRAL MODEL OF GRAPHENE - MASSOU, SIAKA (My University, 2017)
Graphene is basically a single atomic layer of graphite; an abundant minearl which is an allotrope of carbon that is made up of very tightly bonded carbon atoms organized into a hexagonal lattice. the incorporation of magnetism to the long list of graphenecapabilities has been pursued since its first isolation. In this contribution, we examine the magnetic possibilities in graphene using the chiral model. In the framework of the 8-spinor generalization of the scalar chiral model of graphene, we consider the spin and quasi-spin excitations in graphene, the interaction of graphene with uniform magnetic field and use the gauge invariance principale for introducing the electromagnetic interaction. The Lagrangian density of the model is simplified and our graphene material reveals the evident diamagnetic effect: the weakening of the magnetic field within the graphene sample. Therefore, graphene can become an ideal material for studying spin transport (spintronics).
Keywords: Chiral model; graphene; dirac spinors.